Metode Sad Dharma Dalam Penyuluhan Agama Hindu Pada Kantor Kementerian Agama Kabupaten Buleleng - I Putu Suarnaya; Wahyanti Wahyanti (Pasupati, 2022)
This study aims to describe the Sad Dharma method, which is most widely used in Hinduism counseling at the Ministry of Religion of Buleleng Regency, to find out the obstacles faced by Hindu Religion extension workers in the field at the Ministry of Religion of Buleleng Regency, to find out the supporting facilities used by religious instructors Hindus at the Office of the Ministry of Religion of Buleleng Regency. This research is a qualitative descriptive study whose population consists of 55 people consisting of civil servant and non-PNS extension workers at the office of the Ministry of Religion, Buleleng Regency. The technique of determining informants and collecting data is by using quota sampling technique. Data collection was carried out by interviews, library research and document recording methods. And the method of data analysis uses descriptive qualitative techniques accompanied by quantitative data as a reinforcement of the results statement. Based on the results of the research, the following results were obtained: a) an effective method widely used by extension agents of the Ministry of Religion was the dharmawacana method, b) several obstacles were encountered in counseling, namely: a) heterogeneous audiences, b) unfavorable weather, c) facilities and infrastructure such as a sound system is inadequate, d) little space for religious activities to be carried out, e) most of the instructors who are still young lack confidence, f) senior audiences are sometimes selfish and testful, g) training programs are still minimal, h) coaching funds limited number of people have not even been budgeted for, c) Supporting facilities in counseling include religious books and other supporting books and a sound system.